Effectiveness of Bovine Tunica Vaginalis Powder in the Prevention of Tendon Adherence Following Tendon Repair Process in Bucks - Ali Hussein khudair; Hassanain A. Emran (مجلة الانبار للعلوم البيطرية)
The current study was designed to investigate the efficacy of lyophilized bovine tunica vaginalis powder on peritendinous adhesion of induced defect in superficial digital flexor tendon (SDFT) in goats. The study was carried out on 18 adult bucks, the surgical procedure was done under highly aseptic conditions. Prior to surgery, animals were sedated by intramuscular injection of 2 % xylazine in a dose 0.5 mg/kg body weight, then the site of the operation is anesthetized by linear infiltration of 2% lidocaine hydrochloride. The surgical incision is made on the skin on the palmer surface of the metacarpal bone of the left forelimb to expose the (SDFT), a (0.1 depth, 0.2 width, and l Long) cm defect is made on the exposed tendon, this gap is filled with drops of sterile normal saline in (9) animals, and mentioned as a control group, while the gap of the rest (9) animals is filled with the lyophilized powder as treated group. Subcutaneous tissue was closed using absorbable suture material by simple continuous suture technique, and a simple interrupted suture mattress using non-absorbable suture material for closing the skin. The macroscopic findings exhibited a significant difference in adhesion scores between the 2nd, and 3rd periods of assessment post-operation in the first and second groups, with no significant differences between groups. The conclusion of this study is the tunica vaginalis scaffold has no obvious effect on decreasing adhesion between a tendon and surrounding tissues.